2021
DOI: 10.1186/s12870-021-02992-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cell wall-associated kinases as important regulators involved in Gossypium hirsutum resistance to Verticillium dahliae

Abstract: Background Verticillium wilt, caused by the soil borne fungus Verticillium dahliae, is a major threat to cotton production worldwide. An increasing number of findings indicate that WAK genes participate in plant−pathogen interactions, but their roles in cotton resistance to V. dahliae remain largely unclear. Results Here, we carried out a genome-wide analysis of WAK gene family in Gossypium hirsutum that resulted in the identification of 81 putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…To better understand the relationship of the Soltu.DM.02G029720.1 encoded protein with other plant WAK/WAKL proteins, we performed a phylogenetic analysis that includes all the Arabidopsis and tomato WAK/WAKL proteins and several other plant WAK/WAKL proteins shown to have a role in plant resistance against pathogen infection. 7 , 10 , 14 The phylogenetic analysis revealed that the Soltu.DM.02G029720.1 encoded protein is clustered with SlWAKL2 and SlWAKL5 from tomato, GhWAK77 from cotton, AtWAKL14 and AtWAKL21 from Arabidopsis, and OsWAK25 and OsWAKL21.2 from rice ( Figure 1b ). The Soltu.DM.02G029720.1 protein showed the closest similarity to tomato SlWAKL2 (98% similarity), followed by GhWAK77 (73% similarity), SlWAKL5 (72% similarity), and OsWAK25 (68% similarity) and OsWAKL21.2 (55% similarity) from cotton, tomato, and rice, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To better understand the relationship of the Soltu.DM.02G029720.1 encoded protein with other plant WAK/WAKL proteins, we performed a phylogenetic analysis that includes all the Arabidopsis and tomato WAK/WAKL proteins and several other plant WAK/WAKL proteins shown to have a role in plant resistance against pathogen infection. 7 , 10 , 14 The phylogenetic analysis revealed that the Soltu.DM.02G029720.1 encoded protein is clustered with SlWAKL2 and SlWAKL5 from tomato, GhWAK77 from cotton, AtWAKL14 and AtWAKL21 from Arabidopsis, and OsWAK25 and OsWAKL21.2 from rice ( Figure 1b ). The Soltu.DM.02G029720.1 protein showed the closest similarity to tomato SlWAKL2 (98% similarity), followed by GhWAK77 (73% similarity), SlWAKL5 (72% similarity), and OsWAK25 (68% similarity) and OsWAKL21.2 (55% similarity) from cotton, tomato, and rice, respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 25 Plant WAK/WAKL protein sequences included are those encoded by the WAK / WAKL gene family from Arabidopsis and tomato, 5−6 as well as several other plant WAK / WAKL genes demonstrated to have a role in plant disease resistance. 7 , 10–15 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations